2003
DOI: 10.1093/jn/133.10.3215
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Iron Deficiency Alters the Neurochemical Profile of the Developing Rat Hippocampus

Abstract: Cognitive deficits in human infants at risk for gestationally acquired perinatal iron deficiency suggest involvement of the developing hippocampus. To understand the plausible biological explanations for hippocampal injury in perinatal iron deficiency, a neurochemical profile of 16 metabolites in the iron-deficient rat hippocampus was evaluated longitudinally by 1H NMR spectroscopy at 9.4 T. Metabolites were quantified from an 11-24 microL volume centered in the hippocampus in 18 iron-deficient and 16 iron-suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
241
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(268 citation statements)
references
References 56 publications
16
241
2
2
Order By: Relevance
“…Phosphorylethanolamine concentration decreases during cerebral development and this observation is consistent in rodents and humans, paralleling the progression of myelination and cellular proliferation (Blüml et al, 1999;Gyulai et al, 1984;Kulak et al, 2010;Tkáč et al, 2003;Turner et al, 1994;Rao et al, 2003;Wijnen et al, 2010a). Like choline, increased PE metabolism during high cellular proliferation was found in several types of brain tumors and to correlate with tumor malignancy (e.g.…”
Section: Neurotransmitter Metabolismmentioning
confidence: 57%
“…Phosphorylethanolamine concentration decreases during cerebral development and this observation is consistent in rodents and humans, paralleling the progression of myelination and cellular proliferation (Blüml et al, 1999;Gyulai et al, 1984;Kulak et al, 2010;Tkáč et al, 2003;Turner et al, 1994;Rao et al, 2003;Wijnen et al, 2010a). Like choline, increased PE metabolism during high cellular proliferation was found in several types of brain tumors and to correlate with tumor malignancy (e.g.…”
Section: Neurotransmitter Metabolismmentioning
confidence: 57%
“…[9][10][11][12] More recent studies on iron status and the developing brain showed that perinatal iron deficiency affects dendritic growth and structure, neural metabolic activity, and synaptogenesis. [16][17][18]23,24 We hypothesized that these neural processes may also play an important role in determining the effect of low iron on reflexes reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In such models, decreases in brain iron content have been associated with electrophysiological alterations, impaired dopaminergic function, decreased cytochrome c oxidase activity, abnormal dendritic morphology, impaired myelin production, and long-term behavioral changes. [9][10][11][12][13][14][15][16][17][18] Tamura et al 19 has reported that cord serum ferritin levels in term human newborn infants correlated with ultimate cognitive function at 5 years of age. While such correlations do not confirm the causal relationship, given the multiple confounders in such study populations (as noted by Fleming,20 and Beard and Connor 21 ), these data suggest the importance of iron status for the developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo highfield 1 H NMR spectroscopy is a sensitive and noninvasive method that can be used for the simultaneous quantification of multiple metabolites from distinct regions of the developing brain under physiological and adverse perinatal conditions [46,50]. At high magnetic field strengths of 9.4 T, a neurochemical profile consisting of metabolite markers of energy metabolism, neuronal integrity, myelination, and neurotransmitters can be reliably and longitudinally measured from specific brain regions, such as the developing hippocampus [46,50].…”
Section: Introductionmentioning
confidence: 99%